2017
DOI: 10.3390/catal7050166
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Decomposition of N2O over Cu–Zn/ZnAl2O4 Catalysts

Abstract: Abstract:The catalytic decomposition of N 2 O was investigated over Cu-Zn/ZnAl 2 O 4 catalysts in the temperature range of 400-650 • C Catalytic samples have been prepared by wet impregnation method. Prepared catalysts were characterized using several techniques like BET surface area, X-ray diffraction (XRD), and Scanning electron microscopy (SEM). The Cu-Zn/ZnAl 2 O 4 showed higher catalytic performance along with long term stability during N 2 O decomposition. The Cu-Zn/ZnAl 2 O 4 catalysts yielded 100% N 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Under high reaction temperatures, catalysts have a decreased activity and a lower life‐time. Other limitations refer to the lack of studies clarifying which factors significantly influence the catalytic activity of the catalysts, 28 and the high costs of specific catalysts 29 . For instance, zeolite‐based catalyst have deactivation issues when in the presence of high amounts of water and oxygen, and can be used in a limited number of applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under high reaction temperatures, catalysts have a decreased activity and a lower life‐time. Other limitations refer to the lack of studies clarifying which factors significantly influence the catalytic activity of the catalysts, 28 and the high costs of specific catalysts 29 . For instance, zeolite‐based catalyst have deactivation issues when in the presence of high amounts of water and oxygen, and can be used in a limited number of applications.…”
Section: Introductionmentioning
confidence: 99%
“…29 For instance, zeolite-based catalyst have deactivation issues when in the presence of high amounts of water and oxygen, and can be used in a limited number of applications. Research has shown that there are limited studies on the development of N 2 O catalytic decomposition 30.…”
mentioning
confidence: 99%
“…In recent years, many researches have been focused upon the adsorption and decomposition of N 2 O on various catalyst surfaces. Through the experimental studies, it is known that spinel Ni 0.75 Co 2.25 O 4 modified with cesium cations [7], Fe/SSZ-13 [8], Co–Mn–Al mixed oxides [9] and Cu–Zn/ZnAl 2 O 4 [10] have good catalytic effects on the N 2 O decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…The catalyst activity, however, was found to be degraded in the presence of small amounts of oxygen and water vapor in the feed stream [33]. Zheng et al [34]…”
Section: Introductionmentioning
confidence: 99%